Biomarcadores de diagnóstico complementar na Doença de Alzheimer : enfoque em genes que participam da formação da placa beta-amiloide, via do folato e geração de estresse oxidativo - Camporez, Daniela (2018)
Alzheimer Disease (AD) is the most common type of dementia related to aging. It is a serious, chronic and progressive pathology, associated with memory and cognition loss, that leads to death. The mayor risk factor for this disease development is the advanced age, that with a complex interaction of environmental and genetic factors all together can increase the incidence of the disease. Even though its cause is still unknown, the genetic factors and the oxidative stress play an important role in the AD pathogenesis. In this association study we have investigated if polymorphisms in the genes APOE (rs429358 and rs7412 FOXO (rs2802292) MTHFD1L (rs11754661) SERPINA3 (rs4934) SIRT1 (rs2273773) and SOD2 (rs4880) and environmental factors such as: educational level, ethnicity and sex are associated with risk to the AD, in a sample of 332 old individuals from the southest in Brazil (109 individuals with a probably diagnosis of AD and 223 controls – healthy old individuals, paired by age and sex. The genetic polymorphisms were analized through the real time polymerase chain reaction (RT-PCR). In our sample the gene polymorfism APOE showed to be highly associated with the disease, both the genotypes ɛ4ɛ4 and ɛ3ɛ3 proved to be a factor of risk and protection respectively. The GG genotype of the MTHFD1L gene has been shown to be associated with an increased risk of developing Alzheimer's disease. As the genotype GG and AG of the SERPINA3 gene were shown to be protection and risk factors, respectively. The TT and CT genotypes of the SIRT1 gene also showed a correlation with the disease. The educational level showed to be positively associated with the control group individuals, who had a formal education for more than four years. FOXO3 and SOD2 did not prove to be statistically associated with the sample and the disease in question. Our results corroborate other studies demonstrating that the etiology of AD may be involved with the folate pathway, with increased oxidative stress in cells of the central nervous system and supports the participation of beta-amyloid plaque forming proteins in the pathology of AD. These results can be useful in the research of genetic biomarkers to identify individual symptoms before the dementia appears and to offer new data for theraphy in the future, helping in the understanding of this disorder and how to respond to it. These results may be useful in the search for early genetic biomarkers capable of identifying the onset of dementia, and provide new data for therapies in the future, helping to understand this disorder. In addition, they reinforce the hypothesis that several genes are involved in the etiology of AD, a condition characterized by high genomic instability and oxidative stress, which may contribute significantly to the degeneration observed in patients.